Robust computation of minimum-time pacing strategies on realistic road cycling tracks - Dahmen, T.; Brosda, F. (Sportinformatik XI : Jahrestagung der dvs-Sektion Sportinformatik 2016 in Magdeburg, 2016)
In a previous publication (Dahmen, 2012) we compared minimum-time pacing strategies for road cycling time trials for two endurance models: the 3-parameter critical power model (Morton, 1996) and an exertion model by Gordon (2005). For the former model, the problem is singular and only an approximate regularized solution for a synthetic continuously varying slope profile was computed. In this contribution, we improve the parametrization, replacing speed by kinetic energy, and employ advanced numerical methods to compute strategies on realistic tracks with complex height profiles.